Expression profile of nuclear receptors upon epstein — barr virus induced b cell transformation - Yenamandra, S.P.; Lundin, A.; Arulampalam, V.; Yurchenko, M.; Pettersson, S.; Klein, G.; Kashuba, E. (Experimental Oncology, 2009)
Background: Infection of human B cells with Epstein—Barr virus (EBV) induces metabolic activation, morphological transformation, cell proliferation and eventual immortalization. Aim: To identify the nuclear receptors, which are the cellular interaction partners of EBNAs, that will help to elucidate the mechanism of B cell transformation. Methods: We have compared the nuclear receptor profile in the naïve and EBV-transformed B-lymphocytes, using TaqMan LDA microfluidic card technology. Results: Out of 48 nuclear receptor, 17 showed differential expression at the mRNA level. The expression of 5 genes was elevated in EBV-transformed cells, whereas 12 genes were downregulated in lymphoblastoid cells (LCLs). 7 genes were studied at the protein level; 2 genes were up regulated (Nr2F2 and RARA) and 4 genes were down regulated (ERB, NUR77, PPARG, and VDR) in LCLs. Conclusion: The nuclear receptor profiling on EBV infected B cells showed alterations of nuclear receptors expression at both mRNA and protein levels compared with non infected peripheral blood cells. Further analysis on a possible role of each nuclear receptor in EBV induced cell transformation should be performed.